Factors predisposing never-married women to have children in Namibia - Nyathi, Cassandre Simphiwe (My University, 2016)
Context: Generally, marriage has been early and almost universal phenomenon in Sub-Saharan Africa, and this can be seen as an important factor in determining fertility. However, fertility among never-married women is no longer negligible. Non-marital childbearing has increased, as women spend much of their reproductive lives unmarried, while remaining sexually active. Although a number of studies have examined non-marital childbearing, the exploration has been largely on teenagers and adolescent youths. The purpose of this study is to identify the factors predisposing never-married women aged 25−49 to have children. Methodology: This study was a secondary data analysis of the 2006-07 Namibian Demographic and Health Survey data. The study population was never-married women, aged 25−49, with a total weighted sample of 2,121. The dependent variable was never-married fertility, categorised into women who have had no birth and those who have had at least one birth. Age specific fertility rates were calculated using the TFR2 module. Bivariate and multivariate binomial logistic techniques were used to examine the association between independent variables of interest and never-married women’s childbearing experience. Results: The study showed that 79% of never-married women, aged 25−49, had at least one child. Respondents from poor households, less educated respondents, rural dwellers and women from the Herero ethno-linguistic group, were more likely to be never-married mothers. The odds of being a never-married mother increased with age. The results further showed that the likelihood for being a never-married mother was higher among those women who reported ever having used contraception. Furthermore, the results showed that delaying age at sexual debut decreases the probability of being a never-married mother. Conclusion: Childbearing among never-married women is common in Namibia, and with increasing age, the risk of having children outside of marriage increases. The consequences of never-married women’s childbearing should be studied, with a focus on the factors identified to influence their childbearing. Furthermore, policies and programmes addressing never-married women’s fertility should reflect the factors associated with never-married women’s fertility in a context where marriage levels are decreasing and fertility is happening outside of marriage.
A RESEARCH REPORT SUBMITTED TO THE FACULTY OF HUMANITIES, SCHOOL OF SOCIAL SCIENCES, UNIVERSITY OF WITWATERSRAND, JOHANNESBURG, IN THE PARTIAL FULFILMENT OF THE REQUIREMENTS FOR THE DEGREE OF MASTER OF ARTS IN THE FIELD OF DEMOGRAPHY AND POPULATION STUDIES 17 September 2015
Keywords: Unmarried mothers--Namibia; Women--Namibia--Social conditions; Fertility, Human--Namibia